2016
DOI: 10.1038/srep19042
|View full text |Cite
|
Sign up to set email alerts
|

A human monoclonal antibody against HPV16 recognizes an immunodominant and neutralizing epitope partially overlapping with that of H16.V5

Abstract: The presence of neutralizing epitopes in human papillomavirus (HPV) L1 virus-like particles (VLPs) is the structural basis of prophylactic vaccines. An anti-HPV16 neutralizing monoclonal antibody (N-mAb) 26D1 was isolated from a memory B cell of a human vaccinee. The pre-binding of heparan sulfate to VLPs inhibited the binding of both N-mAbs to the antigen, indicating that the epitopes are critical for viral cell attachment/entry. Hybrid VLP binding with surface loop swapping between types indicated the essent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…This result has generated AAV with higher accumulation and penetration to the retina and therefore offers a less invasive intravitreal injection route for ocular gene therapy (Kaever et al, 2016 ). Similarly, the significance of HS in developing antibodies against vaccinia virus A27, human papillomavirus (HPV) has been advocated (Silva et al, 2014 ; Xia et al, 2016 ).…”
Section: Sulfotransferase Generated Heparan Sulfatementioning
confidence: 99%
“…This result has generated AAV with higher accumulation and penetration to the retina and therefore offers a less invasive intravitreal injection route for ocular gene therapy (Kaever et al, 2016 ). Similarly, the significance of HS in developing antibodies against vaccinia virus A27, human papillomavirus (HPV) has been advocated (Silva et al, 2014 ; Xia et al, 2016 ).…”
Section: Sulfotransferase Generated Heparan Sulfatementioning
confidence: 99%
“…The 26D1 human monoclonal antibody recognizes a conformational epitope that partially overlaps that of H16.V5. Regarding the FG loop, out of the 8 binding residues of the H16.V5, only three residues were overlapping with the 26D1, suggesting that human neutralizing monoclonal antibodies could have different interaction with the VLP capsid [24]. To obtain the best mimic of the FG loop, we added two cysteine residues at the N-and C-terminus of the peptide and we applied a cyclization step.…”
Section: Discussionmentioning
confidence: 99%
“…The crystallography model of the HPV16 L1 protein predicts the existence of ve loops (BC, DE, EF, FG, and HI) that are displayed on the surface of assembled capsomers [18]. All conformational epitopes identi ed to date using speci c monoclonal antibodies have been found to reside on one or more hyper variable loops of the L1 protein [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The epitope footprints of four neutralising HPV16 MAbs have recently been resolved using cryo-electron microscope analysis and demonstrated for the first time that, alongside FG and HI loop residues, residues in the DE loop formed the core of each epitope with minor contributions from residues in the BC and EF loops1415. Amino acid residues within the DE loop also formed the majority of the epitope footprint recognised by the HPV16 neutralising human MAb 26D1, which was isolated from a HPV vaccine recipient52. In this present study, we found that the DE loop of HPV31 enhanced cross-neutralising antibody recognition of the HPV31 FG loop within the HPV35 L1 backbone.…”
Section: Discussionmentioning
confidence: 99%